Chronic pain, perceived stress, and cellular aging: an exploratory study - Sibille Kimberly T; Langaee Taimour; Burkley Ben; Gong Yan; Glover Toni L; King Chris; Riley Joseph L; Leeuwenburgh Christiaan; Staud Roland; Bradley Laurence A; Fillingim Roger B (SAGE Publishing, 2012)
Abstract Background Chronic pain conditions are characterized by significant individual variability complicating the identification of pathophysiological markers. Leukocyte telomere length (TL), a measure of cellular aging, is associated with age-related disease onset, psychosocial stress, and health-related functional decline. Psychosocial stress has been associated with the onset of chronic pain and chronic pain is experienced as a physical and psychosocial stressor. However, the utility of TL as a biological marker reflecting the burden of chronic pain and psychosocial stress has not yet been explored. Findings The relationship between chronic pain, stress, and TL was analyzed in 36 ethnically diverse, older adults, half of whom reported no chronic pain and the other half had chronic knee osteoarthritis (OA) pain. Subjects completed a physical exam, radiographs, health history, and psychosocial questionnaires. Blood samples were collected and TL was measured by quantitative polymerase chain reaction (qPCR). Four groups were identified characterized by pain status and the Perceived Stress Scale scores: 1) no pain/low stress, 2) no pain/high stress, chronic pain/low stress, and 4) chronic pain/high stress. TL differed between the pain/stress groups (p = 0.01), controlling for relevant covariates. Specifically, the chronic pain/high stress group had significantly shorter TL compared to the no pain/low stress group. Age was negatively correlated with TL, particularly in the chronic pain/high stress group (p = 0.03). Conclusions Although preliminary in nature and based on a modest sample size, these findings indicate that cellular aging may be more pronounced in older adults experiencing high levels of perceived stress and chronic pain.